2015
DOI: 10.1017/s0029665115002414
|View full text |Cite
|
Sign up to set email alerts
|

Food and nutrition security: challenges of post-harvest handling in Kenya

Abstract: Presently, close to 1 billion people suffer from hunger and food insecurity. Statistics in Kenya indicates that over 10 million people suffer from chronic food insecurity and poor nutrition, 2-4 million people require emergency food assistance at any given time with nearly 30 % of Kenya's children being undernourished, 35 % stunted while micro-nutrient deficiency is wide spread. Key among the challenges contributing to inadequate foods include lack of certified seeds, seasonal production (rain-fed), high post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Dominance of physical hitting of the cowpea as the common method of threshing in this study is consistent with the findings of Gómez [38] and Taruvinga et al [39] who reported the threshing method by beating as popular among cowpea farmers. Popularity of nylon sacs, gunny bags, plastic containers, pots, and reed baskets as the storage containers in the areas of study is concurrent with the findings of Kimiywe [40], who among other postharvest storage containers cited use of storage pots, sacks, woven baskets, and drying methods such as hanging over fireplace, drying by smoking, and solar drying as popularly used containers and methods of drying. Recent studies in Nigeria showed that the traditionally preferred method of storage is use of polyethylene bags but pests have made them to turn to alternatives such as metal drums, Purdue-improved cowpea storage (PICS) bags, and double bags according to Moussa et al [41].…”
Section: Cowpea Seed Production and Postharvest Handlingsupporting
confidence: 64%
“…Dominance of physical hitting of the cowpea as the common method of threshing in this study is consistent with the findings of Gómez [38] and Taruvinga et al [39] who reported the threshing method by beating as popular among cowpea farmers. Popularity of nylon sacs, gunny bags, plastic containers, pots, and reed baskets as the storage containers in the areas of study is concurrent with the findings of Kimiywe [40], who among other postharvest storage containers cited use of storage pots, sacks, woven baskets, and drying methods such as hanging over fireplace, drying by smoking, and solar drying as popularly used containers and methods of drying. Recent studies in Nigeria showed that the traditionally preferred method of storage is use of polyethylene bags but pests have made them to turn to alternatives such as metal drums, Purdue-improved cowpea storage (PICS) bags, and double bags according to Moussa et al [41].…”
Section: Cowpea Seed Production and Postharvest Handlingsupporting
confidence: 64%
“…This study focused on post-harvest technologies of mangoes and maize. For the case of mangoes, losses can be as high as up to 50% of the harvested fruits [3]. This is because mango processing in most parts of Kenya has not been taken into consideration and thus limited investment in agro processing and value addition [4].…”
Section: Introductionmentioning
confidence: 99%
“…This is because mango processing in most parts of Kenya has not been taken into consideration and thus limited investment in agro processing and value addition [4]. Post-harvest technologies used during handling can either maintain or deteriorate the quality of the commodity [3]. For instance during harvesting of mangoes majority of farmers use harvesting methods such as climbing of mango trees, using poles and shaking of trees which exposes the fruits to more mechanical damages [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations